Directionally Solidified Boride and Carbide Eutectic Ceramics. Issue 6 (12th May 2016) - Chen, Wei‐Ting; White, Ryan M.; Goto, Takashi; Dickey, Elizabeth C.
Abstract : Borides and carbides generally have outstanding hardness, excellent wear resistance, and high melting points due to their covalent bonding. Directionally solidified eutectic (DSE) composites of boride and carbide constituent phases have been investigated since the 1970s as an approach to produce dense composite microstructures with added control over the microstructure. A variety of DSE ceramic composites have been developed and evaluated as potential materials for structural and functional applications due to their unique thermo‐electro‐mechanical properties. Renewed interest over the past few decades has been motivated, in part, by the needs for ultrahigh‐temperature composites for aerospace applications along with low‐density composites for armor applications. Some directionally solidified boride and carbide DSEs exhibit advantages in material properties over monolithic materials. This study reviews historical and recent research on processing methods, microstructure, crystallography, and material properties (mechanical, electrical, thermal properties, and oxidation resistance) of directionally solidified boride and carbide eutectic ceramic composites. Opportunities along with current limitations and needs for future developments are also reviewed and discussed.